2011
DOI: 10.1038/onc.2011.220
|View full text |Cite
|
Sign up to set email alerts
|

The autophagy conundrum in cancer: influence of tumorigenic metabolic reprogramming

Abstract: Tumorigenesis is often accompanied by metabolic changes that favor rapid energy production and increased biosynthetic capabilities. These metabolic adaptations promote the survival and proliferation of tumor cells, and in conjunction with the hypoxic and metabolically challenged tumor microenvironment, influence autophagic activity. Autophagy is a catabolic process that allows cellular macromolecules to be broken down and re-utilized as metabolic precursors. Stimulation of autophagy promotes the survival of tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
64
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 108 publications
(99 reference statements)
0
64
0
Order By: Relevance
“…4,10,12 The high proliferation rate of cancer cells, along with the excessive anabolism occurring within the tumor, leads to a limited nutrient accessibility, to a hypoxic context, and to a leak of electrons within the mitochondria of tumor cells. 13 Those conditions partially account for the increased levels of reactive oxygen species (ROS) exhibited by cancer cells, which, in turn, induce additional mutations in the DNA, as well as damage in macromolecules and organelles. 13 Glutamine and leucine are potent inhibitors of macroautophagy (hereafter referred as autophagy), a key catabolic mechanism that cells use to degrade long-lived proteins and organelles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,10,12 The high proliferation rate of cancer cells, along with the excessive anabolism occurring within the tumor, leads to a limited nutrient accessibility, to a hypoxic context, and to a leak of electrons within the mitochondria of tumor cells. 13 Those conditions partially account for the increased levels of reactive oxygen species (ROS) exhibited by cancer cells, which, in turn, induce additional mutations in the DNA, as well as damage in macromolecules and organelles. 13 Glutamine and leucine are potent inhibitors of macroautophagy (hereafter referred as autophagy), a key catabolic mechanism that cells use to degrade long-lived proteins and organelles.…”
Section: Introductionmentioning
confidence: 99%
“…13 Those conditions partially account for the increased levels of reactive oxygen species (ROS) exhibited by cancer cells, which, in turn, induce additional mutations in the DNA, as well as damage in macromolecules and organelles. 13 Glutamine and leucine are potent inhibitors of macroautophagy (hereafter referred as autophagy), a key catabolic mechanism that cells use to degrade long-lived proteins and organelles. 14 The major downstream effector mediating this inhibition is the mechanistic target of rapamycin complex 1 (MTORC1), a central regulator of cell growth, mRNA translation, autophagy, and metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Today, non-physiological alterations of the intracellular redox state are well established hallmarks of tumor biology, due to their implication in several transforming events, such as self-sufficiency in growth signals [2], apoptosis evading [3], sustained angiogenesis [4,5], autophagy [6,7] and tissue invasion [8,9]. This has been exploited by chemotherapeutic strategies based on the use of ROS-generating molecules (e.g., 2-metoxyestradiol and anthracyclins) to selectively kill transformed cells [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro, the scope of autophagic involvement with aspects of the tumorigenic state encompasses links between autophagy and many hallmarks of cancer [e.g., evasion of apoptosis, selfsufficiency in growth signal, and DNA damage stress (4-6)] and the corresponding cancer cell stress phenotypes [e.g., hypoxia, genomic instability, and aneuploidy (6)]. Recent studies have revealed associations between modulated autophagy and a variety of tumor-associated physiologic changes, including restructured stroma (7), altered survival signals (8)(9)(10)(11), angiogenesis in response to hypoxia (12), altered metabolism (13), altered proliferation (14), genomic instability (15), aneuploidy/copy-number variation (16,17), and immune-system modulation (18). In an emerging area of investigation, researchers are conducting comprehensive and unbiased examinations of a multitude of patient samples, including sequence data analyses and transcriptional and translational expression profiling of tumors, to determine whether predicted pathologic autophagy modulation exists in the corresponding human contexts, and, if so, whether and how it influences cancer pathogenesis.…”
Section: Introductionmentioning
confidence: 99%